Clarifying assumptions to enhance our understanding and assessment of clinical reasoning - Durning, Steven J; Artino, Jr, Anthony R; Schuwirth, Lambert; van der Vleuten, Cees (Academic medicine, 2013)
Deciding on a diagnosis and treatment is essential to the practice of medicine. Developing competence in these clinical reasoning processes, commonly referred to as diagnostic and therapeutic reasoning, respectively, is required for physician success. Clinical reasoning has been a topic of research for several decades, and much has been learned. However, there still exists no clear consensus regarding what clinical reasoning entails, let alone how it might best be taught, how it should be assessed, and the research and practice implications therein.In this article, the authors first discuss two contrasting epistemological views of clinical reasoning and related conceptual frameworks. They then outline four different theoretical frameworks held by medical educators that the authors believe guide educators' views on the topic, knowingly or not. Within each theoretical framework, the authors begin with a definition of clinical reasoning (from that viewpoint) and then discuss learning, assessment, and research implications. The authors believe these epistemologies and four theoretical frameworks also apply to other concepts (or "competencies") in medical education.The authors also maintain that clinical reasoning encompasses the mental processes and behaviors that are shared (or evolve) between the patient, physician, and the environment (i.e., practice setting). Clinical reasoning thus incorporates components of all three factors (patient, physician, environment). The authors conclude by outlining practical implications and potential future areas for research.